Task-Based Instruction in teaching 21st Century literature from the Philippines and the world: Learners’ views and reflections - Parcon, Richard Espino (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This study aimed to determine the learners' views and reflections on task-based instruction in teaching 21st Century literature from the Philippines and the World Subject. Specifically, the following objectives were attained: to determine the understanding of learners in the concept of task and task-based instruction, to know learners' perceptions in the implementation of task and task-based instruction used by the teacher in teaching 21st Century Literature subject, to point out the problems encountered by the students and how the students overcome those problems in performing task-based activities. 73 grade 11 students served as the respondents of this study. Using the descriptive method, specifically survey and interview, the study revealed that most students clearly understood the concept of task and task-based instruction. However, some students only agreed that performing tasks and the teacher's task-based instruction in teaching 21st Century Literature use the English language. The majority of the respondents strongly agreed that task and task-based instruction is implemented in their 21st Century Literature class. External factors, language used in the instructions written in the module, interest in literature and familiarity with literary materials, and difficulty level of task-based activities in the module are problems that the respondents encountered during the implementation of task-based instruction in their 21st Century Literature class. While seeking classmates' and teacher's assistance, teacher's motivation and teaching strategies, and self-initiative and motivation are the means for the students to overcome the difficulties they encountered in implementing the task and task-based instruction in 21st Century Literature class.